2012
DOI: 10.4161/psb.20407
|View full text |Cite
|
Sign up to set email alerts
|

Additional cause for reduced JA-Ile in the root of a Lotus japonicus phyB mutant

Abstract: Light is critical for supplying carbon for use in the energetically expensive process of nitrogen-fixing symbiosis between legumes and rhizobia. We recently showed that root nodule formation in phyB mutants [which have a constitutive shade avoidance syndrome (SAS) phenotype] was suppressed in white light, and that nodulation in wild-type is controlled by sensing the R/FR ratio through jasmonic acid (JA) signaling. We concluded that the cause of reduced root nodule formation in phyB mutants was the inhibition o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Nodulation inhibition by JA has recently been reported in Medicago truncatula ( Sun et al, 2006 ) and Lotus japonicus ( Nakagawa and Kawaguchi, 2006 ). EST analysis of Lotus japonica showed that during Rhizobium – Lotus interaction, genes involved in pathogen defense response and JA biosynthetic enzyme (AOC and OPRs) were upregulated and suppressed during the late nodule formation step ( Shigeyama et al, 2012 ; Bordenave et al, 2013 ). According to Kouchi et al (2004) , in the JA biosynthetic pathway, genes responsible for lipooxygenase were mostly downregulated.…”
Section: Jamonates and Physiological Responsesmentioning
confidence: 99%
“…Nodulation inhibition by JA has recently been reported in Medicago truncatula ( Sun et al, 2006 ) and Lotus japonicus ( Nakagawa and Kawaguchi, 2006 ). EST analysis of Lotus japonica showed that during Rhizobium – Lotus interaction, genes involved in pathogen defense response and JA biosynthetic enzyme (AOC and OPRs) were upregulated and suppressed during the late nodule formation step ( Shigeyama et al, 2012 ; Bordenave et al, 2013 ). According to Kouchi et al (2004) , in the JA biosynthetic pathway, genes responsible for lipooxygenase were mostly downregulated.…”
Section: Jamonates and Physiological Responsesmentioning
confidence: 99%
“…The phyB mutant of Lotus japonicus exhibits a constitutive shade avoidance phenotype just as in Arabidopsis but also has a reduced number of nodules compared with WT plants (Figure 3) (Suzuki et al., 2011). Grafting experiments showed that nodulation can be reduced in plants composed of phyB shoots and WT roots, indicating that the mutation in the shoot is sufficient to get the impoverished nodulation phenotype in the roots (Shigeyama et al., 2012, Suzuki et al., 2011). The nodulation deficiency in phyB mutants is associated with decreased root JA levels and a downregulation of JA-responsive gene expression compared with WT roots (Shigeyama et al., 2012, Suzuki et al., 2011).…”
Section: Shade Avoidance Shapes Plant-biotic Interactionsmentioning
confidence: 99%
“…Grafting experiments showed that nodulation can be reduced in plants composed of phyB shoots and WT roots, indicating that the mutation in the shoot is sufficient to get the impoverished nodulation phenotype in the roots (Shigeyama et al., 2012, Suzuki et al., 2011). The nodulation deficiency in phyB mutants is associated with decreased root JA levels and a downregulation of JA-responsive gene expression compared with WT roots (Shigeyama et al., 2012, Suzuki et al., 2011). Interestingly, nodulation by Bradyrhizobium japonicum was promoted by end-of-day (EOD) low R:FR treatment in soybean (Balatti and Montaldi, 1986, Hunt et al., 1990), suggesting that there may be substantial species-specificity of the interplay between light and beneficial interactions.…”
Section: Shade Avoidance Shapes Plant-biotic Interactionsmentioning
confidence: 99%
“…Experimental validation reveals that the nodulation is decreased in grafted plants with phyB shoots and control roots. This is indicative of the fact that the mutations in the shoot tissue decrease nodulation in the roots ( Suzuki et al, 2011 ; Shigeyama et al, 2012 ). The decreased nodulation in phyB mutants can be linked to downregulation of JA-responsive gene expression leading to lower JA levels in roots ( Suzuki et al, 2011 ; Shigeyama et al, 2012 ).…”
Section: Effect Of Dark/light On Plant–pathogen Interaction and Assocmentioning
confidence: 99%
“…This is indicative of the fact that the mutations in the shoot tissue decrease nodulation in the roots ( Suzuki et al, 2011 ; Shigeyama et al, 2012 ). The decreased nodulation in phyB mutants can be linked to downregulation of JA-responsive gene expression leading to lower JA levels in roots ( Suzuki et al, 2011 ; Shigeyama et al, 2012 ). Next, taking into account the impact of R:FR exposures, the plant defense mechanisms against herbivores and pathogens are downregulated under low R:FR conditions ( Ballaré, 2014 ; Ballaré and Austin, 2019 ; Figure 5 ).…”
Section: Effect Of Dark/light On Plant–pathogen Interaction and Assocmentioning
confidence: 99%